2020
DOI: 10.1111/jcmm.15713
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA ADAMTS9‐AS1 suppresses colorectal cancer by inhibiting the Wnt/β‐catenin signalling pathway and is a potential diagnostic biomarker

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…Among the lncRNAs in the frlncRNA signature, several have been demonstrated to be related to immunity, ferroptosis, and malignancy. For instance, ADAMTS9-AS1, which was reported to suppress the malignant phenotypes of breast cancer cells [ 32 ], could also regulate colorectal cancer cell proliferation and migration [ 33 ]. The gene-pair strategy also helped disclose the underlying association between the paired lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Among the lncRNAs in the frlncRNA signature, several have been demonstrated to be related to immunity, ferroptosis, and malignancy. For instance, ADAMTS9-AS1, which was reported to suppress the malignant phenotypes of breast cancer cells [ 32 ], could also regulate colorectal cancer cell proliferation and migration [ 33 ]. The gene-pair strategy also helped disclose the underlying association between the paired lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells proliferation and invasion are important aggressive behavior of human cancers. 13 , 14 A large number of studies have revealed that lncRNA can function as promoter or inhibitor of human cancer proliferation, invasion and it was widely acknowledged that numerous lncRNAs were involved in the progression of CRC. 2 For example, FOXCUT (a novel long noncoding RNA) promotes the colorectal cancer proliferation and invasion through activating FOXC1/PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Its sense transcript, ADAMTS9 (ADAM metallopeptidase with thrombospondin type 1 motif 9), encodes for a disintegrin and metalloproteinase with thrombospondin motifs enzyme; single nucleotide polymorphisms in ADAMTS9 sequence have been associated with cognitive aging [49]. ADAMTS9 suppresses β-catenin and the canonical Wnt signaling pathway [50] that is known to be inhibited in the AD brain [51,52].…”
Section: Discussionmentioning
confidence: 99%